Observation of Mn-Ni-Si-rich features in thermally-aged model reactor pressure vessel steels - Jenkins, BM; Styman, PD; Riddle, N; Bagot, PAJ; Moody, MP; Smith, GDW; Hyde, JM (Elsevier, 2020)
Atom probe tomography was used to characterise two low-Cu (< 0.04 at. %) model steels after exposure to long-term thermal ageing. Mn-Ni-Si-rich features were observed to form after as little as 20,731 h (∼ 2.4 years) of ageing. The composition of these features were compared to those predicted by thermodynamic models and the similarities and differences are discussed.